PCOT: An open‐source toolkit for multispectral image processing - James Finnis; Helen C. Miles; Ariel Ladegaard; Matt Gunn (Geoscience Data Journal)
Abstract PCOT is a Python program and library which allows users to manipulate multispectral images and associated data. It is in active development in support of the ExoMars mission and intended to be used on data from the Rosalind Franklin rover, but it has much greater potential for use beyond this specific context. PCOT operates on a graph model – the data are processed through a set of nodes which manipulate it in various ways (e.g. add regions of interest, perform maths, splice images together, merge image channels, plot spectra). A PCOT document describes this graph, and we intend that documents are distributed along with the data they generate to help reproducibility. PCOT is open‐source, and contributions can be made to the core software, as plugins, or by using PCOT as a library in your own code.